Rola parlamentu w powstaniu ustawy o czasie pracy w przemyśle i handlu z 1919 r. - Baszak, Łukasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
The article presents the role of parliament in the establishment of the Working Time in Industry and Trade Act of 18 December 1919, which played an immensely important role in social legislation during the Second Republic of Poland. The author concludes that as a result of the exceptional situation prevailing in the reconstituted Polish state, it was not the government that played a key role in the creation of the Act, but the Parliament. Although the government issued a decree of 23 November 1918 concerning an 8-hour working day, the decree did not regulate a number of issues related to the length of working time. This was negatively assessed by the parliamentary committees: the Labour Protection Committee and the Industry and Commerce Committee, which created their own bills. In the course of the legislative process, through the speeches of representatives of several political parties, one could see different approaches in dealing not only with the working time, but also with the issues of social legislation, as well as the vision of Poland's economic development in the first years after the regaining of independence.
Keywords: labour law in Second Polish Republic; Working Time in Industry and Trade Act of 1919; social legislation; Legislative Sejm (1919-1922)